Agent-Based Conceptual Framework for Collaborative Educational Resources Adaptation in Virtual Learning Environments - Bremgartner, Vitor; Netto, José Francisco M.; Menezes, Crediné (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2017: Anais do XXVIII Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/cbie.sbie.2017.1087, 2017)
Frequently, the existing resources in Virtual Learning Environments (VLEs), used in distance education courses and blended, are presented in the same way for all students. So, the approach adopted in this paper in order to solve this problem is based on a framework called ArCARE (Conceptual Framework of Educational Resources Adaptation in Virtual Learning Environments), which allows adaptation of resources for students in VLEs. It aims the construction of students’ knowledge, using a multi-agent system technology that handles an open learner model ontology. These ArCARE resources are recommendation and adaptation of collaborative activities such as Pedagogical Architectures for the students have a more effective learning and increase in skills levels of a particular course. Results obtained in a flexible curriculum course of Computational Thinking show the feasibility of the proposal.